Peran Kepala Desa “Desa Siaga” dalam Penanggulangan HIV/AIDS di Kabupaten Pemalang - Susi Kusumawati; Laksmono Widagdo; Harbandinah Pietojo (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2011)
To get public empowerment need of head village role to make conditional village. The research target is to analize influencing factors to head village role of Desa Siaga in HIV/AIDS overcome at Pemalang district. It’s an analytic discriptive research with cross sectional quantitative and qualitative. Sample research is total population of head village second and third level desa siaga at 51 people. Research result with statistic bivariat test chi square look that relation degree of college, long of work, knowledge of desa siaga, knowledge of HIV/AIDS, attitude of desa siaga, attitude of HIV/AIDS, readiness facility and infrastructure and FKD role with head village role in overcome HIV/AIDS. However multivariate test result with regression logistic have result readiness facility and infrastructure desa siaga have tendency 265,837 times bigger to affect head village desa siaga to role good, and the good role of FKD have tendency 167,320 times bigger to affect head village desa siaga to role good in desa siaga and HIV/AIDS overcome.